Pengembangan ICT (Information Communication Technology) sebagai Solusi Inovatif Pembelajaran Bahasa Indonesia di Era Tsunami Digital - Erisy Syawiril Ammah (Tarbiyatuna Kajian Pendidikan Islam, 2017)
This article aims to describe the problems of integrating ICT in learning Indonesian in schools. This study uses observation and open interviews. The school, which became the object of this study is MTsN 3 Banyuwangi. After observation and interviews can be known that ICT can not be optimally integrated in the learning process. Many teachers who do not understand how to innovate ICT to support learning effective and engaging for students. Therefore in this article also presented innovative solutions are offered to be used in solving the problem of integration and the development of ICT, especially in learning Indonesian. Learning innovations included the power point Internet-based learning, facebook based learning, learning, berbagis youtube, email-based learning, learning-based pages, and blogs based learning.